Increasing The Knowledge of Traffic Safety for Early Childhood Through The Game of Traffic Dragon Snake - Farkhati, Naely Ayu; Nugroho, R Agustinus Arum Eka (BELIA: Early Childhood Education Papers, 2020)
This study aims to determine whether there are differences and increased knowledge about road safety for early childhood by implementing the game of the traffic snake in the Panti Puruhita Krapyak Kindergarten, West Semarang, Semarang. This research uses quantitative research in the form of Pre-Experimental Design (non-design) is a one-group pretest-posttest design. The population in this study was Group B students with a total of 44 students at the Panti Puruhita Krapyak Kindergarten. The instrument in this study was a scale of knowledge about road safety for early childhood. The sampling technique in this study uses random sampling. The data collection techniques used in this study were interviews, observation, and documentation. The data analysis used is the paired sample t-test. Based on the results of the statistical calculation of the t-test using paired sample t-test obtained sig (2-tailed) 0,000 <0.05 and the calculated t value of -28.421, so that the value of t-count (-28.421) <-t table (-2.045). It means that there are significant differences in knowledge about road safety for early childhood between before and after being treated. While the result of the percentage of the increase in knowledge about road safety is 81.09%, with a mean value of pre-test at 76.17 and post-test at 131.17, so the difference obtained is 55. It means that knowledge about road safety for early childhood experiences significant improvement after being given treatment through the game of Traffic Dragon Snake. Knowledge of traffic safety after being treated is higher than before being treated. It can be concluded that the game of the traffic snake is effective to increase knowledge about road safety for young childhood in Panti Puruhita Krapyak kindergarten, West Semarang, Semarang.